Mapping nursing interventions using the Therapeutic Intervention Scoring System in bloodless liver transplantations. (December 2020) - Rengeiné, T.K.; Tihanyi, E.; Dinya, E.; Smudla, A.; Kóbori, L.; Kanizsai, P.; Fazakas, J.
Abstract: Background: The Simplified Therapeutic Intervention Scoring System adapted to liver transplantation by King's College Hospital rank 138 activities to determine the nursing workload, diagnostic, monitoring and therapeutic needs. Objectives: To evaluate nursing activities of "King's-TISS" score grouped in organ systems and nurse patient ratio in the perioperative 48 hours of blood product free liver transplantations (LT). Methods: The "King's-TISS" score's were analysed by nursing procedures and grouped, scored according to organ systems. The nursing workloads were studied during LT (T1), on arrival on the ICU (T2) and 12–24-48 hours after LT (T3-T4-T5). Results: The total of "King's-TISS" score points were decreased by ≥20% daily (p = 0.001). The mean score of 104 ± 3.5 points (CI:104–105) during LT decreased to 84.7 ± 12 points (CI:83–86) in 48 hours (T5). The "metabolic" and "haemostasis" points increased (p = ).01), the "immunology" points unchanged (T2-T5) postoperatively. A slight decrease was observed in case of "basic nursing care", "monitoring", "neurologic support", "renal support" and "cardiovascular support" points (T2-T5, p < .01). The "invasive intervention" and "ventilatory support" points strongly decreased (T2-T5, p < .001). One "King's-TISS" point was found to equal 7.4 minutes with a nurse patient ratio of 2:1 intraoperatively and 1:1 postoperatively. Conclusion: Absence of blood product administration in LT decreases the total and organ specific workload, except the metabolic, haemostasis, immunology and basic support requirement. It was not within the scope of the King's-TISS score to analyse the application of viscoelastic haemostasis test and coagulation factor concentrate administration.